2017
DOI: 10.1519/jsc.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Handgrip Strength and Sport Performance

Abstract: Cronin, J, Lawton, T, Harris, N, Kilding, A, and McMaster, DT. A brief review of handgrip strength and sport performance. J Strength Cond Res 31(11): 3187-3217, 2017-Tests of handgrip strength (HGS) and handgrip force (HGF) are commonly used across a number of sporting populations. Measures of HGS and HGF have also been used by practitioners and researchers to evaluate links with sports performance. This article first evaluates the validity and reliability of various handgrip dynamometers (HGD) and HGF sensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
163
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 154 publications
(147 reference statements)
5
163
2
2
Order By: Relevance
“…The current study is among a few comparing metrics of HGS with common North American football performance measures. The results of the current study were contrary to those previously reported (Ağbuğa et al, 2009;Cronin et al, 2017;Shields et al, 1984;Straub, 1979). In a review by Cronin et al (2017) only a few studies of North American football player performance variables and HGS measures were referenced.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The current study is among a few comparing metrics of HGS with common North American football performance measures. The results of the current study were contrary to those previously reported (Ağbuğa et al, 2009;Cronin et al, 2017;Shields et al, 1984;Straub, 1979). In a review by Cronin et al (2017) only a few studies of North American football player performance variables and HGS measures were referenced.…”
Section: Discussioncontrasting
confidence: 99%
“…As HGS is an indicator of overall strength, it follows that it has also been shown to be a predictor of sporting ability in a variety of different sports. A recent meta-analysis of the role of HGS in sport performance examined HGS's role in predicting sport performance, and its' correlation to performance indicators in combat sports, ball sports, field sports, and strength sports (Cronin et al, 2017). HGS was found to be predictive of sporting ability in combat and strength sports, but not in ball or field sports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand grip has previously been used to predict muscle strength and endurance, and increased hand grip strength is associated with increased upper body strength [33,34]. Gymnasts require a high grip strength to be able to perform well in their events, and aerial athletes require some level of grip strength to perform on their apparatuses as well [2,33]. When compared to female gymnasts, the aerialists presented with an average, but 66% lower grip strength [35].…”
Section: Discussionmentioning
confidence: 99%
“…(Strand et al, 2016) In Sports science the value of strength and isometric training have been traditionally used to prevent and treat sport injuries, talent detection and general performance improvement in sports. (Cronin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%